Utilizing lifetime performance measures on fed cattle to evaluate management strategies for the cow-calf producer - Slattery, Roberta M. (Kansas State University, 2010)
Newer marketing techniques and production technologies have made large amounts of data available in fed cattle production that previously were not available to the cow-calf producer. The application of this data in breeding and management practices has only begun to be evaluated. This research used individual records, taken from birth to slaughter, on 6,360 calves from a single cow-calf producer who retained ownership of the calves through a custom feed yard and marketed them in a grid system. Using this information, four major topics were analyzed; identifying profitability drivers among animal characteristics, assessing weaning weight as a predictor of finished performance, utilizing lifetime performance of calves to evaluate cow productivity, and quantifying the effects of illness on cattle efficiency and carcass quality. The main profitability driver was hot carcass weight, while avoiding quality and yield grade discounts was also imperative to returns. Weaning weight did not prove to be a highly accurate tool to predict the finished quality and profitability of an animal. Evaluations of cow performance based on calf productivity were accomplished, accounting for all variation possible, however since sires were not known these performance evaluations may not be capturing an accurate picture of maternal influence on calf genetics. Performance evaluations can still be useful, but it is suggested that they not be the basis for all culling and replacement decisions. Evaluating calves based on the age of their dam highlights a peak in performance in most all measures when a cow is 7 years old. Illness in the feedlot linearly affected Net Return in a negative fashion and also negatively influenced Return to Ranch. This was mostly related to losses in efficiency, but also losses in hot carcass weight and dressing percentage in highly treated animals.
Keywords: Beef cattle evaluation; Fed cattle profitability; Cattle performance; Agriculture, General (0473); Economics, Agricultural (0503)